Activated Protein C Ameliorates Diabetic Cardiomyopathy via Modulating OTUB1/YB-1/MEF2B Axis - Zhong, Xiaodan; Wang, Tao; Xie, Yang; Wang, Mengwen; Zhang, Wenjun; Dai, Lei; Lai, Jinsheng; Nie, Xiang; He, Xingwei; Madhusudhan, Thati; Zeng, Hesong; Wang, Hongjie (Frontiers in Cardiovascular Medicine, 2021)
Abstract Aims The pathogenesis of diabetic cardiomyopathy (DCM) is complex and the detailed mechanism remains unclear. Coagulation protease activated Protein C (aPC) has been reported to have a protective effect in diabetic microvascular disease. Here, we investigated whether aPC could play a protective role in the occurrence and development of major diabetic complication DCM, and its underlying molecular mechanism. Methods and Results In a mouse model of streptozotocin (STZ) induced DCM, endogenous aPC levels were reduced. Restoring aPC levels by exogenous administration of zymogen protein C (PC) improved cardiac function of diabetic mice measured by echocardiography and invasive hemodynamics. The cytoprotective effect of aPC in DCM is mediated by transcription factor Y-box binding protein-1 (YB-1). Mechanistically, MEF2B lies downstream of YB-1 and YB-1/MEF2B interaction restrains deleterious MEF2B promoter activity in DCM. The regulation of YB-1 on MEF2B transcription was analyzed by dual-luciferase and chromatin immunoprecipitation assays. In diabetic mice, aPC ameliorated YB-1 degradation via reducing its K48 ubiquitination through deubiquitinating enzyme otubain-1 (OTUB1) and improving the interaction between YB-1 and OTUB1. Using specific agonists and blocking antibodies, PAR1 and EPCR were identified as crucial receptors for aPC’s dependent cytoprotective signaling. Conclusion These data identify that the cytoprotective aPC signaling via PAR1/EPCR maintains YB-1 levels by preventing the ubiquitination and subsequent proteasomal degradation of YB-1 via OTUB1. By suppressing MEF2B transcription, YB-1 can protect against DCM. Collectively, the current study uncovered the important role of OTUB1/YB-1/MEF2B axis in DCM and targeting this pathway might offer a new therapeutic strategy for DCM. Translational Perspective DCM is emerging at epidemic rate recently and the underlying mechanism remains unclear. This study explored the protective cell signaling mechanisms of aPC in mouse models of DCM. APC, a former FDA approved anti-sepsis drug, along with its derivatives can be applied from bench to bed and can be explored as a new strategy for personalized treatment for DCM. Mechanistically, OTUB1/YB-1/MEF2B axis plays a critical role in the occurrence and development of DCM and offer a potential avenue for therapeutic targeting of DCM.